TRPM channels in human cancers: regulatory mechanism and therapeutic prospects - Qinfeng Liu; Mengyu Hu; Shi Li; Xin Zhang; Rui Zhang; Hao Lyu; Shuai Xiao; Dong Guo; Xing-Zhen Chen; Jingfeng Tang; Cefan Zhou (Biomarker Research)
Abstract The transient receptor potential melastatin (TRPM) channel family has been previously implicated in various diseases, including those related to temperature sensing, cardiovascular health, and neurodegeneration. Nowadays, increasing evidence indicates that TRPM family members also play significant roles in various types of cancers, exhibiting both pro- and anti-tumorigenic functions. They are involved in tumor cell proliferation, survival, invasion, and metastasis, serving as potential diagnostic and prognostic biomarkers for cancer. This paper begins by describing the structure and physiological functions of the TRPM family members. It then outlines their roles in several common malignancies, including pancreatic, prostate, colorectal, breast, brain cancer, and melanoma. Subsequently, we focused on investigating the specific mechanisms by which TRPM family members are involved in tumorigenesis and development from both the tumor microenvironment (TME) and intracellular signaling. TRPM channels not only transmit signals from the TME to regulate tumor cell functions, but also mediate extracellular matrix remodeling, which is conducive to the malignant transformation of tumor cells. Importantly, TRPM channels depend on the regulation of the inflow of various ions in cells, and participate in key signaling pathways involved in tumor progression, such as Wnt/β-catenin, MAPK, PI3K/AKT, p53, and autophagy. Finally, we summarize the current strategies and challenges of targeting TRPM channels in tumor treatment, and discuss the feasibility of combining targeted TRPM channel drugs with cancer immunotherapy.